Effect of Mn pre-partition before cold rolling on austenite reversion and mechanical properties of 3.5Mn steel. (7th February 2022) - Kang, Tao; Liang, Juhua; Zhao, Zhengzhi; Zhang, Lei; Hou, Xiaoying
ABSTRACT: In this paper, two kinds of cold-rolled 3.5Mn steels with different initial microstructures are designed. Combined with EBSD and dilatometer, the effect of Mn pre-partition on the austenite reversion and the mechanical properties in the subsequent intercritical annealing process are compared. The results show that the Mn pre-partition can significantly increase the austenite reversion rate, achieve a large amount of austenite formed in a short time isothermal process, and provide a sustained TRIP effect for the material during the tensile process. In the end, the specimen of HR700CR710 achieved excellent mechanical properties with yield strength of 1034 MPa, tensile strength of 1146 MPa, total elongation of 28.7%, and the product of strength and elongation of 32.9 GPa %.